2015
DOI: 10.1089/ham.2015.0036
|View full text |Cite
|
Sign up to set email alerts
|

Stunting and the Prediction of Lung Volumes Among Tibetan Children and Adolescents at High Altitude

Abstract: Weitz, Charles A., and Ralph M. Garruto. Stunting and the prediction of lung volumes among Tibetan children and adolescents at high altitude. High Alt Biol Med 16: [306][307][308][309][310][311][312][313][314][315][316][317] 2015.-This study examines the extent to which stunting (height-for-age Z-scores £ -2) compromises the use of low altitude prediction equations to gauge the general increase in lung volumes during growth among high altitude populations. The forced vital capacity (FVC) and forced expiratory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 51 publications
2
5
0
1
Order By: Relevance
“…Stunting influenced deviations from predicted lung function values among 208 stunted and 365 non-stunted children in Tibet. These differences were compatible with the effects of retarded growth and lung maturation characteristic among stunted children 19 .…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…Stunting influenced deviations from predicted lung function values among 208 stunted and 365 non-stunted children in Tibet. These differences were compatible with the effects of retarded growth and lung maturation characteristic among stunted children 19 .…”
Section: Resultssupporting
confidence: 78%
“…The effect of stunted height on lung function growth is further compounded by maturational delays, particularly during the onset of adolescent growth spurt in stature. During puberty, dysynaptic growth appears to be more conspicuous in stunted children as compared to normal children, as stunted children are not only shorter but also more likely to exhibit delayed increment in muscular strength and lung maturation 19 , 65 , 66 . However, while the phenotypic correlates of stunting recede due to rapid catch up growth during early childhood, indicators of restrictive lung function persist late into the life course.…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence of short stature will be overestimated. The solutions for this are to build growth reference based on the same area population or lower the cut-off value to diagnose short stature in these places 48. We must be more prudent when we diagnose short stature of children from these areas and avoid excessive laboratory tests or therapy for these children.…”
Section: Discussionmentioning
confidence: 99%
“…Our study indicated that children who lived in high-altitude places had a high risk of short stature, which generally applied to other individuals residing in such areas—Peruvians and Tibetans (2, 20), who live in the Andes and Himalayas, respectively, with an average elevation above 4,000 m. Another study focused on the growth retardation of children aged 0–36 months in Tibet showed that with an increase in altitude (3,000 to 4,500 m), the prevalence and odds ratio of stunting gradation increased—this phenomenon was not observed in underweight and wasting (42). This result was also confirmed by studies involving children in Argentina and other countries (43, 44), and may be partly attributed to the negative correlation between birth weight and altitude, where intrauterine growth restrictions result in oxygen deficit and the effect of cytokines, endothelin, etc.…”
Section: Discussionmentioning
confidence: 58%